Numerical investigation on cavitating jet inside a poppet valve with special emphasis on cavitation-vortex interaction. (October 2019) - Yuan, Cong; Song, Jinchun; Zhu, Lisha; Liu, Minghe
Highlights: Elongation of vortical cavitation due to vortex shearing effect. Absence of axially-aligned cavity in transitional region. Suppression of vorticity due to cavitation growth for transitional cavitating jet flow. Abstract: A thorough understanding of the internal flow dynamics inside a poppet valve makes sense for an improved control performance. Hence, a numerical simulation for the cavitating jet is performed with main concern on the cavitation-vortex interaction. The periodic cavitation structure, along with corresponding variation in vorticity distribution and large scale eddy, is presented for the quasi-steady flow from numerical results. As expected, cavitation inception exhibits great dependence on coherent structure, which is organized as paired vortex rings. Besides, cavitation is persistently located at core of vortex, indicating strong correlation between cavitation and vortex dynamics. The cavitation-vortex correlation is further discussed with analysis of vorticity transport equation, involving vortex stretching, dilatation and baroclinic torque terms. At incepting stage, vortex stretching is the dominant factor, responsible for vortex growth and the elliptical shape of cavitation ring. In comparison, the dilatation term could produce either enhancement or suppression in local vorticity, depending on the volumetric variation induced by cavitation. During the collapse stage, the bubble collapse creates baroclinic vorticity, and contributes to 3-dimensional vorticity. The most significant finding of the present study is the suppression of vorticity during the growing process of cavitation, contributing to an enhanced understanding of the cavitation-vortex interaction.